PENERAPAN SANKSI PIDANA ADAT TERHADAP PELAKU ZINA DI WILAYAH KENAGARIAN GARAGAHAN KECAMATAN LUBUK BASUNG KABUPATEN AGAM - Handoko, Bobi; Effendi, Erdianto; Hendra, Rahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Indonesia is a country of law (rechstaat) that where any provision of law tolean or guided by the Pancasila and the 1945 Constitution, as a rule it must notconflict with higher laws as they apply nationally. But in social life other thannational laws that are also laws that grow and thrive in a society, in which the lawwas born of habits or attitudes and behavior of society itself is often referred to asthe customs. Custom or habit is what will develop into a provision calledcustomary law. That customary law and traditional criminal law is still used incertain areas. Particularly in the area Kenagarian Garagahan Agam District ofLubuk cone, where people still use traditional criminal law to resolve crimes ofadultery.In this study the authors used the method of sociological writing is research inthe form of empirical studies and legislation to find theories about the process andthe effectiveness of the enactment or rule of law in society.The conclusions that can be drawn on this issue, namely, that the applicationof criminal sanctions such as discarded or customary in fines still can not beoptimally applied, because of the people who most fear or do not report to thehead of customs about the incident so that the head of their own customs can notapply The traditional criminal law. Advice given writer is the author suggests thatin the preparation of the national Criminal Code should pay attention to the valuesprevailing in the midst of society. In addition, for law enforcement is expected tobe able to act fairly in the imposition of sanctions for adultery.Keywords: Application - Sanctions - Criminal Indigenous - Adultery